Micro Finance Loans and Financial Performance of Small and Medium Enterprises in Sembabule District. A Cross-sectional Study. - Abomugisha , Vincent; Birungi , Miria; Atubasise , Joseph; Bakashaba , Edmand (Student's Journal of Health Research Africa, 2022)
Background This study aimed at examining the relationship between loan access and the financial performance of SMEs in the Sembabule district; the relationship between microfinance lending terms and the financial performance of Small and Medium Enterprises in the Sembabule district, and the relationship between Microfinance loan sizes and the financial performance of SMEs. Methodology The study used a descriptive, correlational, and cross-sectional survey design. The study sample size was 53 SMEs within the district to establish the relationship between the study variables and use self-administered questionnaires and interviews to collect relevant data for this study. Results Of the 50 respondents to the study, 30 were females and 20 were males. This shows that the majority 60% of the respondents were females and 40% were males. The correlational findings revealed a spearman’s co-efficient of -0.242 with a Sig value of 0.117. This shows a negative weak relationship between loan access and the financial performance of SMEs in the Sembabule district. The spearman’s correlation coefficient of 0.724 was revealed with a significant value of 0.004. This shows a strong positive relationship between lending terms and financial performance. Therefore favorable lending terms led to the improved financial performance of SMEs in the Sembabule district. Conclusion: Generally, microloan access, lending terms, and loan size have a significant relationship with the financial performance of SMEs in the Sembabule district. Recommendations: SMEs should avoid taking loans that take a sizable proportion of their business as this affects decision-making, operations, and financial performance of the business. The loan should be kept below 15% of the total capital of the business.